2005
DOI: 10.1590/s1415-43662005000400029
|View full text |Cite
|
Sign up to set email alerts
|

Parâmetros de conforto térmico e fisiológico de ovinos Santa Inês, sob diferentes sistemas de acondicionamento

Abstract: Através do presente trabalho, objetivou-se determinar os parâmetros fisiológicos e produtivos e os índices de conforto térmico em ovinos da raça Santa Inês, criados em dois apriscos, um coberto com telha de barro (TBA) e o outro com telha de fibrocimento (TFC), no município de São João do Cariri, nos meses de agosto a outubro de 2003. Utilizaram-se 20 animais machos, castrados e distribuídos em baias individuais. Os índices ambientais analisados foram a temperatura ambiente, do globo negro, umidade relativa do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0
13

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 3 publications
1
8
0
13
Order By: Relevance
“…The period of the afternoon was characterized by a situation of thermal discomfort. The results found in this study were lower than those found by CEZAR et al (2004) and similar to those reported by Oliveira et al (2005). According to Ferreira (2005), very low relative humidity can promote the dissipation of heat through the evaporative process, but it also may cause heat stress through the dryness of mucous membranes and respiratory tract, in addition to promoting an increase in solid particles in suspension.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…The period of the afternoon was characterized by a situation of thermal discomfort. The results found in this study were lower than those found by CEZAR et al (2004) and similar to those reported by Oliveira et al (2005). According to Ferreira (2005), very low relative humidity can promote the dissipation of heat through the evaporative process, but it also may cause heat stress through the dryness of mucous membranes and respiratory tract, in addition to promoting an increase in solid particles in suspension.…”
Section: Resultssupporting
confidence: 66%
“…OLIVEIRA et al (2005) considered that CTR up to 520 W m -2 features an uncomfortable situation for heat sheep in semi-arid northeast. MORAES et al (2004), by analyzing the effect of season on the characteristics of thermoregulation goats in the semiarid region, noted that both the dry season, as the rainy season, the values of CTR were higher than those considered suitable for goats.…”
Section: Resultsmentioning
confidence: 99%
“…Segundo SOUZA et al (2002), existem limites de ITGU definidos para diversas espécies de animais, como a de bovinos, pelo National Weather Service -USA, estando em análise os índices de ITGU para outras espécies de interesse zootécnico. De acordo com a citação de vários autores (CESAR et al, 2004;OLIVEIRA et al, 2005;SANTOS et al, 2006;ANDRADE et al, 2007), em trabalhos com ovinos na região semiárida nordestina, valores de ITGU acima de 78 foram considerados como fora da zona de conforto térmico para ovinos, apesar de ainda não ter classificação definitiva, principalmente com animais nativos da região. Tomando-se por base essas citações, observa-se que, às 11; 13 e 15 h, os valores do ITGU (80,1; 81,3 e 82,1, respectivamente) estiveram acima da zona de conforto térmico para ovinos.…”
Section: Resultsunclassified
“…The resistance of an animal to high temperatures is defined by the greater or lower ability to dissipate excessive body heat, thus managing to keep their average body temperature within the limits of homeothermy Medeiros et al (2007). Rectal temperature is a good indicator of body temperature (Oliveira et al, 2005). According Cesar et al (2004).…”
Section: Resultsmentioning
confidence: 99%
“…The high environmental temperature, humidity and direct sunlight are the main responsible for the discomfort that leads animals to adopt behavioral and physiological measures to maintain homeothermy, which implies the reduction of productive performance (Souza et al, 2010). When a sharp rise in air temperature occurs, the thermoregulatory mechanisms are activated, increasing heat loss in callously through sweating and increasing RF (Oliveira et al, 2005).…”
Section: Resultsmentioning
confidence: 99%